Crystallization and preliminary X‐ray analysis of RabX3, a tandem GTPase from Entamoeba histolytica. Issue 7 (1st July 2014) - Kumar Srivastava, Vijay; Chandra, Mintu; Datta, Sunando
<x xml:space="preserve">Abstract</x> Ras superfamily GTPases regulate signalling pathways that control multiple biological processes by modulating the GTP/GDP cycle. Various Rab GTPases, which are the key regulators of vesicular trafficking pathways, play a vital role in the survival and virulence of the enteric parasite Entamoeba histolytica. The Rab GTPases act as binary molecular switches that utilize the conformational changes associated with the GTP/GDP cycle to elicit responses from target proteins and thereby regulate a broad spectrum of cellular processes including cell proliferation, cytoskeletal assembly, nuclear transport and intracellular membrane trafficking in eukaryotes. Entamoeba histolytica RabX3 (EhRabX3) is a unique GTPase in the amoebic genome, the only member in the eukaryotic Ras superfamily that harbours tandem G‐domains and shares only 8–16% sequence identity with other GTPases. Recent studies suggested that EhRabX3 binds to a single guanine nucleotide through its N‐terminal G‐domain (NTD), while the C‐terminal G‐domain (CTD) plays a potential role in binding of the nucleotide to the NTD. Thus, understanding the intermolecular regulation between the two GTPase domains is expected to reveal valuable information on the overall action of EhRabX3. To provide structural insights into the inclusive action of this unique GTPase, EhRabX3 was crystallized by successive micro‐seeding using the vapour‐diffusion method. A complete data set was collected to 3.3 Å resolution using a single native EhRabX3 crystal at 100 K on BM14 at the ESRF, Grenoble, France. The crystal belonged to monoclinic space group C2, with unit‐cell parameters a = 198.6, b = 119.3, c = 89.2 Å, β = 103.1°. Preliminary analysis of the data using the Matthews Probability Calculator suggested the presence of four to six molecules in the asymmetric unit.